Feminism and the Politics of Childhood Friends or Foes? - Rosen, Rachel; Twamley, Katherine (UCL Press, 2018)
Feminism and the Politics of Childhood offers an innovative and critical exploration of perceived commonalities and conflicts between women and children and, more broadly, between various forms of feminism and the politics of childhood. This unique collection of 18 chapters brings into dialogue authors from a range of geographical contexts, social science disciplines, activist organisations, and theoretical perspectives. The wide variety of subjects include refugee camps, care labour, domestic violence and childcare and education. Chapter authors focus on local contexts as well as their global interconnections, and draw on diverse theoretical traditions such as poststructuralism, psychoanalysis, posthumanism, postcolonialism, political economy, and the ethics of care. Together the contributions offer new ways to conceptualise relations between women and children, and to address injustices faced by both groups.